2002
DOI: 10.5194/angeo-20-1377-2002
|View full text |Cite
|
Sign up to set email alerts
|

Positive storm effects in the dayside polar ionospheric F-region observed by EISCAT and ESR during the magnetic storm of 15 May 1997

Abstract: Abstract. EISCAT/ESR radar data and in situ FAST and PO-LAR satellite observations are coordinately analyzed to investigate positive ionospheric storm effects in the dayside upper F-region in both the polar cap and the auroral oval during the magnetic storm of 15 May 1997. An ionization enhancement, lasting for about 2.5 h, appeared first over the EIS-CAT site around magnetic noon; about one hour later, a similar ionization enhancement was also seen over ESR. During the concerned time period ion energy spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…An increase of DfoF2 on all ionosondes of the chain can be seen from 09:00 UT. A cause of the DfoF2 increase on the northern ionosondes is particle precipitation during the substorm expansive phase as shown in Ma et al (2002). A similar effect on the middle latitude ionosondes, as discussed just above, can be an F2 layer lift due to electrical fields and southward winds (Buonsanto, 1999).…”
Section: European Ionosonde Chainmentioning
confidence: 89%
See 2 more Smart Citations
“…An increase of DfoF2 on all ionosondes of the chain can be seen from 09:00 UT. A cause of the DfoF2 increase on the northern ionosondes is particle precipitation during the substorm expansive phase as shown in Ma et al (2002). A similar effect on the middle latitude ionosondes, as discussed just above, can be an F2 layer lift due to electrical fields and southward winds (Buonsanto, 1999).…”
Section: European Ionosonde Chainmentioning
confidence: 89%
“…Published by Elsevier Ltd. All rights reserved. doi:10.1016/j.asr.2010.08.013 Ma et al, 2002;Yeh et al, 1994). However, these investigations are not enough and many questions are still unanswered.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ma et al [6] concluded that ionization enhancement observed by the EISCAT radar might be probably caused by soft particles from the magnetosheath precipitating into the F-region ionosphere. The coincidence increase in electron temperature at the EISCAT gives additional evidence for soft particle precipitation.…”
Section: Introductionmentioning
confidence: 98%
“…During the strong magnetic storm of 15 May 1997, positive storm effects were observed by both the European Incoherent SCATter radar (EISCAT) and the ESR radars in the dayside ionospheric F-region, which was superposed on a negative effect background [6] . Ma et al [6] concluded that ionization enhancement observed by the EISCAT radar might be probably caused by soft particles from the magnetosheath precipitating into the F-region ionosphere.…”
Section: Introductionmentioning
confidence: 99%